Adsorption of parabens in aqueous solution onto β-cyclodextrin cross-linked polymer / Chin Yuk Ping - Chin, Yuk Ping (2013)
β-cyclodextrin cross-linked polymers were prepared from hexamethylene diisocyanate (HMDI) and toluene-2,6-diisocyanate (TDI) as a cross-linker. Two types of polymers were synthesized, namely β-CD-HMDI and β-CD-TDI. The polymers were characterized and β-CD-TDI with the molar ratio of 1:7 for β-CD:TDI was chosen for further studies as it gave the highest adsorption of parabens. The adsorption mechanisms were studied with adsorption kinetic models and adsorption isotherm models. Kinetic study was done for single paraben solutions and a mixture of four parabens solution. For the kinetic study, the experimental data were analysed using pseudo-first-order, pseudo-second-order, and intraparticle diffusion kinetic models. Adsorptions follow pseudo-second-order model in both solutions and follow intraparticle diffusion model in a solution mixture of a mixture of four parabens solution. This shows that mechanism of adsorption is affected by the competition among parabens molecules. Langmuir and Freundlich isotherm model were used to further describe the process of adsorption. The two isotherm models are applicable onto the adsorption process for different types of paraben in different condition. The same polymer was reused for nine regenerations in the same conditions to study how effective the recycled polymer was for paraben removal. Adsorption capacities are between 75.6 to 112.8% after regeneration. β-CD-TDI were applied on 10 real aqueous samples and all show positive results.